Percentile distribution of blood pressure readings in relation to body mass index: a populationbased cross-sectional study ADOPOLNOR - Krzyżaniak, Alicja; Stawińska-Witoszyńska, Barbara; Kaczmarek, Maria; Krzywińska-Wiewiorowska, Małgorzata; Siwińska, Aldona (Anthropological Review, 2015)
Recent upward trends toward elevated blood pressure and increased weight expressed in terms of body mass index in children and adolescents call for regular monitoring of their physical growth and age-related changes in blood pressure. This requires adequate tools – reference values of a normal blood pressure range. The main objective of this study was to provide sex- and BMI-specific percentile reference values for systolic and diastolic blood pressure based on the adolescent Polish population, participants in the ADOPOLNOR study. A cross-sectional survey was carried out on a representative, randomly selected cohort of 4,941; 2,451 male and 2,490 female students aged 10–18 years, residents in Wielkopolska province and its capital, the city of Poznań. All examinations were performed in school nursery rooms during morning hours according to standard procedures. Body height and weight were measured and BMI was calculated. Blood pressure was measured twice on each occasion on the right arm using a fully calibrated TECH MED TM-Z mercury gauge sphygmomanometer with sets of exchangeable cuffs and a clinical stethoscope. The blood pressure classification was determined using the surveillance method. For each participant, the mean of measurements taken on each of the three occasions was calculated and served as his/her final blood pressure value. Using the LMS method, fitted percentile curves were created for BMI-related systolic and diastolic blood pressure. The findings revealed that age related blood pressure pattern was similar in boys and girls. It showed a steady increase of systolic and diastolic blood pressure with age. There was a positive correlation between the systolic and diastolic blood pressure indicating that when systolic blood pressure increased so diastolic did (r=0.61 at p<0.01). Boys were likely to have relatively higher mean values of systolic and diastolic blood pressure and steeper slope for BMI-related change in blood pressure than girls. Similar pattern was found for age-related changes in BMI. The quotation of 3rd, 5th, 10th, 15th, 25th, 50th, 75th, 85th, 90th, 95th, and 97th at any given BMI between 12 kg/m2 and 35 kg/m2 provided indication of the entire variation in blood pressure of adolescent males and females aged 10–18 years. The sex- and BMI-specific reference values and charts for systolic and diastolic blood pressure may be a useful tool in monitoring blood pressure for early detection of its abnormal level and treatment of children and adolescents with high blood pressure.